Strategi Guru dalam Menumbuhkan Nilai Kebersamaan pada Pendidikan Multikultural di Sekolah Dasar - Syahrial Syahrial; Agung Rimba Kurniawan; Alirmansyah Alirmansyah; Arahul Alazi (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2019)
Based on observations at SDN 47 / IV Jambi City, there are various Malay, Minang, Batak, Javanese and Betawi cultures. Although different students are not different from each other in the learning process or in groups, students help each other if there is a group that is experiencing difficulties in the learning process. This study aims to describe the teacher's strategy in growing togetherness for students in multicultural education in elementary schools. Suggestions used are qualitative ethnographic types. The research informants were IVC grade teachers. Research instruments: observation, interview and documentation. After the data is obtained it will be analyzed using the Miles and Huberman technique (reduction, display, verification). The results of the study are teacher strategies in growing togetherness values ​​in multicultural education, namely 1). Introducing the background of each student, 2). Bring students' familiarity through interviewing students to get to know each other better with one another 3). Placing sitting in class by changing 4). Form discussion groups from different ethnic groups. 5). Getting used to mutual cooperation in class or outside the classroom.